2006
DOI: 10.1556/avet.54.2006.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of neosporosis in beef and dairy cattle breeds in Northeast Hungary

Abstract: In order to assess the seroprevalence of bovine neosporosis with indirect fluorescent antibody test (IFAT), blood samples were collected randomly from 1063 beef and dairy cattle belonging to 12 different breeds in Northeast Hungary. Antibodies to Neospora caninum were detected in 27 (2.5%) of the animals, kept on 19 of the 42 settlements included in this survey. Since samples were collected on 50 farms, herd prevalence amounted to 38%. The percentage of cattle with seroconversion increased with age, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
9
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
3
9
3
Order By: Relevance
“…The seroprevalence (27.7%) in 3 counties (Arad, Bihor, and Timiş) was lower, however, than that previously reported in cattle with reproductive problems from dairy farms in central and northern regions of the country (55.9%; Gavrea and Cozma, 2010). Compared to several other European countries, our seroprevalence was higher than that reported in Slovakia (20.1%; Reiterová et al, 2009) and Hungary (2.5%; Hornok et al, 2006), similar to that found in the northwest of Spain (23.2%; Eiras et al, 2011) but lower than that reported in Italy (32.0%; Rinaldi et al, 2007) and Turkey (46.5%; Kul et al, 2009).…”
supporting
confidence: 75%
See 1 more Smart Citation
“…The seroprevalence (27.7%) in 3 counties (Arad, Bihor, and Timiş) was lower, however, than that previously reported in cattle with reproductive problems from dairy farms in central and northern regions of the country (55.9%; Gavrea and Cozma, 2010). Compared to several other European countries, our seroprevalence was higher than that reported in Slovakia (20.1%; Reiterová et al, 2009) and Hungary (2.5%; Hornok et al, 2006), similar to that found in the northwest of Spain (23.2%; Eiras et al, 2011) but lower than that reported in Italy (32.0%; Rinaldi et al, 2007) and Turkey (46.5%; Kul et al, 2009).…”
supporting
confidence: 75%
“…0.05) was found between the seroprevalence of N. caninum antibodies associated with the breed of the animals. Several studies have shown that dairy cattle are more susceptible to N. caninum than are beef cattle (Bartels et al, 2006;Hornok et al, 2006;Rinaldi et al 2007), and vice versa (Eiras et al 2011), but breed-related susceptibility to infection was not demonstrated; in addition, the role of farm dogs was not investigated in these studies.…”
mentioning
confidence: 95%
“…ND = not done; -(negative); + (positive); JER (Jersey); HOL (Holstein); J/H (Jersey/Holstein); Legend for histopathology: 0, absent; +, discrete; ++, moderate; +++, severe; IHC = Immunohistochemistry; +1= positive in the myocardium; +2=positive in the cerebrum. (DUBEY et al, 2007;HORNOK et al, 2006). It has been demonstrated that sero-prevalence might increase with the age and the number of gestations in beef and dairy cattle (DUBEY et al, 2007;HORNOK et al, 2006), suggesting that horizontal transmission is of importance in cattle herds.…”
Section: Discussionmentioning
confidence: 99%
“…(DUBEY et al, 2007;HORNOK et al, 2006). It has been demonstrated that sero-prevalence might increase with the age and the number of gestations in beef and dairy cattle (DUBEY et al, 2007;HORNOK et al, 2006), suggesting that horizontal transmission is of importance in cattle herds.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon might represent the manifestation associated with each management system, i.e., the differences between having or not access to infectious sources, the nutritional differences and emphasis of production activity (such as milking, weaning), or the variability in the duration of time during which the animals are maintained within breeding programs. However, breed predisposition for N. caninum infection cannot be excluded and should be further investigated (Hornok et al 2006). …”
Section: Discussionmentioning
confidence: 99%